Execution Of Rights Under The Designation Of Liability By Auction Of State Court Of Pekalongan - Eka Hendra Muspiyanto; Tutut Suciati Handayani; Gunarto Gunarto (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
This researchaims to determine how the execution Encumbrance through an auction to be determined by the District Court of Pekalongan and what weaknesses and execution Mortgage solution through an auction to be determined by the District Court of Pekalongan. Mortgage execution through an auction based on the determination District Court of Pekalongan held upon the request of the winning bidder. Request execution Mortgage by auction by the auction winner made after terlelang not willing to vacate voluntarily execution object. Mortgage weakness execution through an auction based on the determination that the District Court Pekalongan there are two opinions on the application process execution Encumbrance through an auction to be determined by the District Court if there is a lawsuit against the object of the auction following the application execution. The first opinion the petition can still be processed until the issuance of the determination of the District Court. The second opinion request for execution should be delayed pending completion of a lawsuit against the auction object. This is due to the absence of explicit provision governing the execution Mortgage application process through the auction in case there is a lawsuit in the execution object, especially if there is a lawsuit against the object of execution in case the application execution has been carried out. Similarly, in the case of the emergence of a lawsuit before the application for execution is done. Whether the execution can be carried out or not. This gives rise to a variety of opinions that may be detrimental to the winning bidder. For it should be no explicit provision governing the execution Mortgage application process through the auction in case there is a lawsuit in the execution object other drawback is the resistance of the current terkesekusi will be executed.Keywords: Execution; Mortgage; Auctions; Determination.